Adjectival word order system in English and malay : a typological study - Muhammad Syafiq bin Ramli (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
This study is an effort to investigate the adjectives for both English and Malay; their word order positions and how the positions affect the message they convey. This typological study will be of help to learners engaged in acquiring the two languages simultaneously; it enables them to understand the different structures of the languages thus guiding them to deploy the structures better. The research design of this study uses a meaning-based framework, a move away from syntactical investigation. The meaning arising from the use of all the 11 different types of adjectives of both languages remain the focus. The results show a stark contrast of the use of adjectives in English and Malay. A majority of the adjectives in English are prenominal while those of Malay are postnominal. A small number of postnominal adjectives in English and the availability of prenominal adjectives in Malay prove that both types do exist, albeit in limited quantities. The positions of the adjectives in English do affect the message of the tokens. In other words, the prenominal adjectives convey one set of meaning whilst the postnominal another. However, the positions of the adjectives in Malay do not show a similar range in meaning, i.e. the position and the corresponding meanings as found in the Huffman framework do not apply to Malay. The conclusion is quite apparent in that differing positions convey meaning in English; but this is not so in Malay.